A Review of Recent Developments in Advanced Computational Intelligence and Intelligent Informatics - An, Jianqi; Chen, Xin; Wu, Min; She, Jinhua (Journal of advanced computational intelligence and intelligent informatics, 2016)
The theory and application of advanced computational intelligence and intelligent informatics has been one of the most active fields of research over the last decades. A significant number of methods have been proposed to effectively solve problems of clustering, image processing, optimization, bio-information understanding, and modeling and control. They have been applied to many areas, including complex industrial processes and economics. This paper presents a review of the articles and papers addressing advanced computational intelligence and intelligent informatics from the Journal of Advanced Computational Intelligence and Intelligent Informatics in the past two years.